KUALITAS ES KRIM DENGAN PENAMBAHAN TEPUNG BIJI SALAK PONDOH (Salacca edulis Reinw.) SEBAGAI STABILIZER - Sinung Pranata (Universitas Pelita Harapan, 2020)
Ice cream is a frozen food that in process of its making requires a stabilizer to get a soft texture and can hold on at room temperature. Salak pondoh seed flour has glucomannan content which can be used as a stabilizer. This study was conducted to determine the quality of ice cream using variations in salak pondoh seed flour’s concentration from chemical, physical and micorbiological quality and to determine optimum concentration of salak pondoh seed flour as stabilizer to replace CMC. Complete Random Design (CRD) with 4 variation concentrations of salak pondoh seed flour, i.e 0 % (CMC as control); 0,15 %; 0,30 % and 0,45 %. The results shows that salak pondoh (Salacca edulis Reinw.) seed flour not contribute to protein content and total solids, overrun and colors, total plate count and Salmonella of ice cream, but contributing to the fat content and melting quality of ice cream so the best quality from chemical, physical dan microbiological quality is ice cream with the addition of salak pondoh seed flour 0,45 % and can be concluded that salak pondoh seed flour can be used as CMC.